PERTUMBUHAN Streptococcus mutans PADA BIOAKTIVITAS EKSTRAK RIMPANG LENGKUAS SECARA in vitro DAN PEMANFAATANNYA SEBAGAI ZAT AKTIF PADA PASTA GIGI - iurlina Siregar; Ferdinand Saras Dhiksawan; Anna Farida (Jurnal Kimia (Journal of Chemistry), 2011)
The study aims to (i) isolate white galangal (Alpinia galanga) and red (Alpinia purpuruta) rhizome extract compound, (ii) examine its bioactivity against Staphylococcus mutans, and (iii) investigate its usage as an active substance in tooth paste in the laboratory. The result of the study indicates that the extract of n-hexane of red galangal has a higher bioactivity effect against Staphylococcus aureus compared to the white one. The examination of the experimental tooth paste with an addition of 1 % active substance (extract of n-hexane, namely D and J fractions) indicates that the diameter of resistance against Staphylococcus aureus formed by D fraction is higher (15.5 mm) than the positive control (15 mm). Meanwhile, an addition of active substance of 1.5 % D and J fractions indicates a higher diameter of resistance (16.2 mm and 14.7 mm) compared to positive control.. IR and GC-MS analysis indicates that the most dominant compound existing in D fraction is 2-metil -1-(o-tolil)pentanol, while the most dominant compound in the J fraction is 2--ethyl-5-methyl benzoic acid.